Challenging Cases and Complication Management in Pain Medicine (Springer International Publishing, 2018)
This comprehensive book provides reviews of pain management complications that arise in clinical practice. Organized into sections focused on types of pain therapy and procedures, each chapter is based on actual complications; starting with a case description that delineates the context with a short past medical and surgical history, pain management technique and outcome it is followed by a comprehensive review of the topic described in the first section. Authors emphasize the elements of differential diagnosis that pointed towards establishing of the complication and describe the best way to treat the identified complication. Physicians treating pain patients will be presented the necessary tools in identifying and treating unanticipated complications following pain interventions, thus providing safer care for their patients.